Comparison of three serological tests applied to diagnosis of the Brucella canis infection in dogs - Azevedo, Sérgio Santos de (2004)
The agar gel immunodiffusion test (AGID), agar gel immunodiffusion test in sera treated by 2-mercaptoethanol (ME-AGID) and complement fixation test (CFT), applied to diagnosis of the canine brucellosis due to Brucella canis, were compared. For this purposes, 80 blood samples from dogs were collected during the rabies vaccination campaign of Santana de Parnaíba municipality, State of São Paulo, in August 1999. The antigens used in the AGID and ME-AGID tests were lipopolysaccharides and proteins from Brucella ovis, strain Reo 198, and in the CFT, the antigen employed was Brucella ovis, strain 63/290. The serological tests were compared two by two by Mc Nemar test, and the agreement was analyzed by the Kappa indicator. The agreement between the CFT and ME-AGID was moderate (Kappa = 0.54), between the AGID and CFT was fair (Kappa = 0.36) and between the AGID and ME-AGID was fair (Kappa = 0.39).